LIFE INSURANCE IN A TESTAMENTARY CLAUSE - Costa, Deborah Regina Lambach Ferreira; Diniz, Maria Helena (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2026)
This article addresses the issue arising from the modification of life insurance beneficiaries by final will dispositions and the validity of a testamentary clause that determines, by the will of the testator, that the entire capital to be received upon redemption of the life insurance or personal accidents, be used to pay debts and taxes such as IR (income tax), IPTU (real estate tax), IPVA (vehicles tax), social security contributions, private sector debts, among other liabilities. By doing so, wouldn’t the insured party be entitled to future funds that won’t be part of his/her assets (estate) at the time of death, and that were not inventoried at the time? Ultimately, would a testamentary clause that “empties” the value of the capital stipulated by the testator upon his/her death to settle debts with creditors beyond the inheritance’s resources? What would be the limits of dispositions, of last will, imposed by the insured married spouse under partial property regime, taking into account the community property of the surviving spouse, as well as the legitimate status of the necessary heirs in their responsibilities for the debts of the deceased? This research employs descriptive and deductive methodologies, grounded in a doctrinal, legislative, and judicial bibliographical review. In order to achieve this, the fundamental concepts of institutions such as inheritance and community property, as well as the legal nature and purpose of the life insurance contract, will be elucidated. Subsequently, the rights of widow/widower as a surviving spouse entitled to half of the marital assets shall be assessed, and the responsibilities of the widower/widow and heirs for the debts of the deceased will then be discussed. Finally, the relationship between the principle of respect for human dignity, the right to life, and the right to housing will be addressed in order to conclude that such testamentary clauses are invalid for violating article 794 of the Civil Code and for failing to meet the socioeconomic and axiological purposes of the law.